2022
DOI: 10.3847/2041-8213/aca145
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Missing Baryons in the Intergalactic Medium with Localized Fast Radio Bursts

Abstract: The missing baryon problem is one of the major unsolved problems in astronomy. Fast radio bursts (FRBs) are bright millisecond pulses with unknown origins. The dispersion measure of FRBs is defined as the electron column density along the line of sight, and accounts for every ionized baryon. Here we measure the baryon content of the universe using 22 localized FRBs. Unlike previous works that fixed the value of dispersion measure of FRB host galaxies and ignored the inhomogeneities of the intergalactic medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…They found that these uncertainties have almost no effect on the final Ω b constraint. Given the fact that our f IGM constraint is almost the same as that of Yang et al (2022), we can come to the same conclusion. Note that since the DM IGM distributions are given in discrete redshifts (Zhang et al 2021), we extrapolate them to the redshifts of the localized FRBs through cubic spline interpolation.…”
Section: Frb Dmssupporting
confidence: 55%
See 2 more Smart Citations
“…They found that these uncertainties have almost no effect on the final Ω b constraint. Given the fact that our f IGM constraint is almost the same as that of Yang et al (2022), we can come to the same conclusion. Note that since the DM IGM distributions are given in discrete redshifts (Zhang et al 2021), we extrapolate them to the redshifts of the localized FRBs through cubic spline interpolation.…”
Section: Frb Dmssupporting
confidence: 55%
“…The uncertainties of these best-fit parameters may impact our final f IGM constraint. To investigate whether the uncertainties of these parameters affect the Ω b constraint (similar to our f IGM constraint), Yang et al (2022) derived Ω b using the best-fit values of these parameters plus or minus the uncertainties. They found that these uncertainties have almost no effect on the final Ω b constraint.…”
Section: Frb Dmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DM is the integral over the number density of free electrons along the propagation path between the source and observer, which contains important information on the cosmological distance. Therefore, the combined DM and redshift information of FRBs can be used to study cosmology, such as constraining the baryon number density of the Universe (Deng & Zhang 2014;McQuinn 2014;Macquart et al 2020;Yang et al 2022), the dark energy equation of state (Gao et al 2014;Zhou et al 2014;Walters et al 2018;Wei et al 2018;Zhang & Li 2020;Zhao et al 2020;Qiu et al 2022), cosmic reionization history (Deng & Zhang 2014;Zheng et al 2014;Hashimoto et al 2021), cosmic proper distance (Yu & Wang 2017), the baryon mass fraction in the intergalactic medium (IGM; Li et al 2019Li et al , 2020Walters et al 2019;Wei et al 2019;Wang & Wei 2023), the Hubble constant (Hagstotz et al 2022;James et al 2022b;Wu et al 2022), and so on. Additionally, strongly lensed FRBs have also been proposed for probing the nature of compact dark matter (Muñoz et al 2016;, for measuring the Hubble constant and cosmic curvature (Li et al 2018), and for determining the post-Newtonian parameter (Abadi & Kovetz 2021;Gao et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found in both simulations (Xia et al 2021) and observations (Wang et al 2021, SDSS) that net rotations of cosmic filaments themselves are non-zero, making them the largest known structures in the Universe to rotate. Cosmic filaments also host the majority of the baryons at low redshifts in the form of the warm-hot intergalactic medium, thereby potentially solving the socalled "missing baryon problem" (Klar & Mücket 2012;Yang et al 2022;Chaves-Montero & Hearin 2021).…”
Section: Introductionmentioning
confidence: 99%